Exploring opportunities and challenges to the adoption of blockchain technology in the fresh produce value chain - Ralph Kwadwo Osei; Marco Medici; Martin Hingley; Maurizio Canavari (AIMS Agriculture and Food, 2021)
This study investigates the attitudes and perceptions of businesses and consumers towards the application of Blockchain technology (BCT) to fresh produce supply chains. Semi-structured interviews and focus groups (FG) were performed with fresh produce company managers and consumers, respectively. The fresh produce sector, in this context, concerns the fresh and chill chain, value-added vegetables, fruits and salads and the ingredients of these used in further food value-added processes and products. A total of five themes were identified as factors influencing BCT adoption: the novelty of the technology, supply chain characteristics, open data issues, cost-benefit analysis, and role of public stakeholders. From these, twelve sub-themes were developed and discussed. Findings provide a framework with opportunities and challenges that the fresh produce system must face in adopting decentralised systems for managing supply chain data like BCT.